1995
DOI: 10.1210/jcem.80.2.7852540
|View full text |Cite
|
Sign up to set email alerts
|

The human Leydig insulin-like (hLEY I-L) gene is expressed in the corpus luteum and trophoblast.

Abstract: A novel member of the insulin superfamily has previously been shown to be expressed only in porcine pre and postnatal Leydig cells and its human analogue demonstrated in the human testes but not in other organs and hence has been tentatively termed Leydig insulin-like peptide (Ley I-L). However, we have detected hLey I-L gene expression in the cyclic human corpus luteum and trophoblast by the reverse transcriptase-polymerase chain reaction (RT-PCR), with primers selected from the published human Ley I-L sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 7 publications
0
24
1
1
Order By: Relevance
“…16 It also is the predominant negative regulator of iron absorption in the small intestine, iron transport across the placenta, and iron release from macrophages. 17 It is noteworthy that the synthesis of hepcidin also is stimulated by inflammation. Hepcidin has not yet been studied in the context of breast carcinoma, but it is an intriguing candidate for m/z 2790.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 It also is the predominant negative regulator of iron absorption in the small intestine, iron transport across the placenta, and iron release from macrophages. 17 It is noteworthy that the synthesis of hepcidin also is stimulated by inflammation. Hepcidin has not yet been studied in the context of breast carcinoma, but it is an intriguing candidate for m/z 2790.…”
Section: Discussionmentioning
confidence: 99%
“…Ley I-L/INSL3 is a member of the insulin superfamily and is expressed only in the human testes, corpus luteum, and trophoblasts, but not in other organs or tissues (including normal or neoplastic breast tissues); therefore, this molecule is not a likely candidate. 17 A third possibility is that the m/z 2790 peak represents the cleavage product of a larger protein.…”
Section: Discussionmentioning
confidence: 99%
“…INSL3 is primarily a reproductive hormone and was first cloned from testicular cDNA libraries (Adham et al, 1993;Pusch et al, 1996). The peptide is secreted by testicular Leydig cells (Adham et al, 1993;Pusch et al, 1996) but is also found in human cyclic corpora lutea (Tashima et al, 1995); ruminant ovary, uterus, and placenta (Bathgate et al, 1996;Roche et al, 1996); mouse (Zimmermann et al, 1997); and marmoset ovary (Zarreh-Hoshyari-Khah et al, 1999). Importantly INSL3 is a circulating hormone in both males (Foresta et al, 2004) and females (AnandIvell et al, 2013), although the levels are much higher in males.…”
mentioning
confidence: 99%
“…Tashima et al (1995), however, were able to show a weak northern signal in human ovary and trophoblast, and Zimmermann et al (1997) detected a similar signal in the mouse ovary. However, neither of these signals were comparable in magnitude to those identified in the ruminant ovary (Bathgate et al, 1996;Roche et al, 1996).…”
Section: Ovarian Expressionmentioning
confidence: 86%
“…Except in the human where a very weak signal is detectable in trophoblast (Tashima et al, 1995), northern hybridization has consistently failed to show any specific RLF transcripts in any tissues other than testis or ovary. In a more extensive study of bovine tissues using RT-PCR, Bathgate et al (1996) were able to detect RLF specific signals in endometrium and myometrium of the uterus both in the cycle and in pregnancy, and in caruncle and chorion, as well as in epididymis.…”
Section: Other Tissuesmentioning
confidence: 96%